Świadectwo nawrócenia w przekazie katechetycznym - Mirosław Gogolik (Colloquia Theologica Ottoniana, 2016)
Contemporary catechetical ministry of the Church as a whole evangelistic subject come under constant reflection, and thus looks for new solutions for more effective education and upbringing. This reflection is also carried out within the study of language catechesis and catechetical forms of media content, which the foundation is undoubtedly the understanding of man, his dignity and identity. Among developed through centuries of linguistic tools and forms of communication of God’s Word, there is space testimony of faith and conversion, which stimulates the listener properly articulated in religious development and proper fruitful transformed by faith. In this paper we look at the use of certificates in catechesis, as a form of media catechetical content, taking particular account of conversion to the faith.